OoNomfundo: a teacher raised by teachers - Jonas, Khanyiso (Multilingual Margins: A journal of multilingualism from the periphery, 2024)
Background: The inspiration for this reflection piece originates from dialoguesn shared with colleagues over mealtimes at the 2022 Learning and Teaching Arts Faculty Writing Retreat for early career researchers and academics. As an early career academic, researcher and relatively newly appointed member of the Linguistics Department at the University of the Western Cape at the time of the retreat, it was these moments that allowed me to find my feet in what was initially a daunting experience. Through the conversations, laughter and sometimes tears, we began to share pieces of ourselves - from the commonality of our present daily personal lives right to our lived experiences and histories.